Keabsahan Pemakaian Yurisprudensi Dalam Perkara Perkawinan Beda Agama Pada Putusan Hakim Nomor 916/PDT.P/2022 PN. Surabaya - Achmad Fathoni; Miftahul Ulum (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2024)
Interfaith Marriage is a classic issue in Indonesian law. There are always pros and cons in society, particularly in cases where Muslims marry individuals of different religions. A recent case involves an interfaith marriage approved by the Surabaya District Court with decision number 916/Pdt.P/2022. In the history of resolving interfaith marriages, judges often refer to the jurisprudence of the Supreme Court Decision No. 1400K/PDT/1986, which allows civil registry offices to record interfaith marriages. This article aims to understand the rules for using jurisprudence in judges' decision-making and to analyze the validity of using jurisprudence in the interfaith marriage case of Surabaya District Court number 916/Pdt.P/2022. This study is a literature review with a qualitative method and a normative-juridical analysis approach. The conclusion of this study is that judges are generally allowed and authorized to use jurisprudence in their decisions as long as it complies with applicable regulations, in this case, the existence of a legal vacuum regarding interfaith marriages. To mitigate the pros and cons in society and provide legal certainty, it is necessary to establish clear regulations concerning the legal status of interfaith marriages.